Hadith #70 - Sahih al-Bukhari - Abu al-Walid أبو الوليد - بركة المجاشعي (Sahih al-Bukhari)
`Abdullah used to give a religious talk to the people on every Thursday. Once a man said, “O Aba `Abdur-Rahman! (By Allah) I wish if you could preach us daily.” He replied, “The only thing which prevents me from doing so, is that I hate to bore you, and no doubt I take care of you in preaching by selecting a suitable time just as the Prophet (ﷺ) used to do with us, for fear of making us bored.”
Grade: Sahih

Hadith #226 - Sahih al-Bukhari - Abu al-Walid أبو الوليد - بركة المجاشعي (Sahih al-Bukhari)
Abu Musa Al-Ash`ari used to lay great stress on the question of urination and he used to say, “If anyone from Bani Israel happened to soil his clothes with urine, he used to cut that portion away.” Hearing that, Hudhaifa said to Abu Wail, “I wish he (Abu Musa) didn’t (lay great stress on that matter).” Hudhaifa added, “Allah’s Messenger (ﷺ) went to the dumps of some people and urinated while standing.”
Grade: Sahih

Hadith #341 - Sahih al-Bukhari - Abu al-Walid أبو الوليد - بركة المجاشعي (Sahih al-Bukhari)
Abu Musa said to `Abdullah bin Mas`ud, “If one does not find water (for ablution) can he give up the prayer?” `Abdullah replied, “If you give the permission to perform Tayammum they will perform Tayammum even if water was available if one of them found it cold.” Abu Musa said, “What about the statement of `Ammar to `Umar?” `Abdullah replied, “`Umar was not satisfied by his statement.”
Grade: Sahih

Hadith #758 - Sahih al-Bukhari - Abu al-Walid أبو الوليد - بركة المجاشعي (Sahih al-Bukhari)
A man came to Ibn Mas`ud and said, “I recited the Mufassal (Suras) at night in one rak`a.” Ibn Mas`ud said, “This recitation is (too quick) like the recitation of poetry. I know the identical Suras which the Prophet (ﷺ) used to recite in pairs.” Ibn Mas`ud then mentioned 20 Mufassal Suras including two Suras from the family of (i.e. those verses which begin with) Ha, Meem (which the Prophet (ﷺ) used to recite) in each rak`a.
Grade: Sahih

Hadith #791 - Sahih al-Bukhari - Abu al-Walid أبو الوليد - بركة المجاشعي (Sahih al-Bukhari)
Hudhaifa said, “I saw a person not performing his bowing and prostrations perfectly. When he completed the prayer, I told him that he had not prayed.” I think that Hudhaifa added (i.e. said to the man), “Had you died, you would have died on a tradition other than that of the Prophet (ﷺ) Muhammad.”
Grade: Sahih

Hadith #1386 - Sahih al-Bukhari - Abu al-Walid أبو الوليد - بركة المجاشعي (Sahih al-Bukhari)
Hudhaifa said, “`Umar said, ‘Who amongst you remembers the statement of Allah’s Messenger (ﷺ) (p.b.u.h) about afflictions’?’ I said, ‘I know it as the Prophet (ﷺ) had said it.’ `Umar said, ‘No doubt, you are bold. How did he say it?’ I said, ‘A man’s afflictions (wrong deeds) concerning his wife, children and neighbors are expiated by (his) prayers, charity, and enjoining good.’ (The sub-narrator Sulaiman added that he said, ‘The prayer, charity, enjoining good and
Grade: Sahih

Hadith #1540 - Sahih al-Bukhari - Abu al-Walid أبو الوليد - بركة المجاشعي (Sahih al-Bukhari)
(One day) I sat along with Shaiba on the chair inside the Ka`ba. He (Shaiba) said, “No doubt, `Umar sat at this place and said, ‘I intended not to leave any yellow (i.e. gold) or white (i.e. silver) (inside the Ka`ba) undistributed.’ I said (to `Umar), ‘But your two companions (i.e. The Prophet (ﷺ) and Abu Bakr) did not do so.’ `Umar said, They are the two persons whom I always follow.’ “
Grade: Sahih